2018
DOI: 10.1111/dom.13416
|View full text |Cite
|
Sign up to set email alerts
|

An integrative systems biology approach for precision medicine in diabetic kidney disease

Abstract: Current therapeutic approaches are ineffective in many patients with established Diabetic Kidney Disease (DKD) disease, an epidemic affecting one in three patients with diabetes. Early identification of patients at high risk for progression and individualizing therapies have the potential to mitigate kidney complications due to diabetes. To achieve this, a better understanding of the complex pathophysiology of DKD is needed. A system biology approach integrating large scale omic data is well suited to unravel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 68 publications
0
18
0
Order By: Relevance
“…A systems biology approach, combining multiomics information, has been suggested as the way forward to better combine and understand information provided by the molecular biomarkers at different stages of disease as well as providing the platform for design of individualized treatment. Mulder et al . provide an in‐depth overview of an approach trying to integrate data from different candidate markers to be used for prediction of both risk and treatment response.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…A systems biology approach, combining multiomics information, has been suggested as the way forward to better combine and understand information provided by the molecular biomarkers at different stages of disease as well as providing the platform for design of individualized treatment. Mulder et al . provide an in‐depth overview of an approach trying to integrate data from different candidate markers to be used for prediction of both risk and treatment response.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…Likewise, not all DM patients with microalbuminuria progress to macroalbuminuria or ESRD (some patients even revert and the microalbuminuria disappears). Therefore, more broad-based approaches including systems biology and multiple omics are being applied to understanding DN pathological mechanisms today [1719].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies in recent times have reported the discovery and validation of non-invasive biomarkers for predicting disease progression and response to treatment in DKD. [23,24] However, these studies need further validation for implementation in clinical practice. With various novel pharmacological agents such as baricitinib, a selectively Janus kinase 1 inhibitor; ruboxistaurin, a protein kinase c β inhibitor; pentoxyphylline, an anti-inflammatory and antifibrotic agent; currently under trial, [25] a miracle drug for Diabetic Kidney Disease is not far away.…”
Section: Discussionmentioning
confidence: 99%